Marine phenolic compounds: Sources, commercial value, and biological activities - Fallas Rodríguez, Pilar (2023)
The commercial value of phenolic compounds has increased in recent years due to their inherent health-related benefits. Marine phenolics are found in diverse natural sources such as seawater, macro- and microalgae, cyanobacteria, seaweeds, seagrasses, and sponges. Seaweed or marine algae extracts containing phenolic compounds have been patented and commercialized. These extracts have been applied to enhance various products in several industries, such as food and beverages, cosmetics and personal care, pharmaceutical, agricultural, and horticulture. Marine phenolic-enriched products have been commercialized by claiming several biological activities like antidiabetic, antiobesity, antihyperlipidemic, anticholesterolemic, cardioprotective, antihypertensive, neuroprotective, antioxidant, antiaging, and photoprotective. Commercial products such as food supplements and cosmetics have been obtained mainly from phloroglucinol and phlorotannin extracts. This chapter reviews the commercial value, uses, and applications of the most relevant phenolic compounds from marine sources.